2021
DOI: 10.1002/mds.28464
|View full text |Cite
|
Sign up to set email alerts
|

MIND and Mediterranean Diets Associated with Later Onset of Parkinson's Disease

Abstract: A BS TRACT: Background: The MIND diet has been linked with prevention of Alzheimer's disease and cognitive decline but has not been fully assessed in the context of Parkinson's disease (PD). The objective of the present study was to determine whether MIND diet adherence is associated with the age of Parkinson's disease onset in a manner superior to that of the Mediterranean diet. Methods: Food Frequency Questionnaires from 167 participants with PD and 119 controls were scored for MIND and 2 versions of Mediter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 36 publications
0
51
0
Order By: Relevance
“…The increasing trends indicated that current strategies were still ill-prepared for the population aging. The findings indicated that active strategies should be adopt to cope with the problems caused by PD, including healthcare and security systems, civil health promotion plan, and healthy lifestyle (66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…The increasing trends indicated that current strategies were still ill-prepared for the population aging. The findings indicated that active strategies should be adopt to cope with the problems caused by PD, including healthcare and security systems, civil health promotion plan, and healthy lifestyle (66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…Future research needs to consider the role of other co-factors such as environmental and lifestyle variables that could influence brain atrophy and functional outcomes in PD together with biological sex. In this context, diet quality and physical activity have shown a protective effect against the development of PD (Yang et al, 2015 ; Liu et al, 2021 ), and MIND and Mediterranean diets has been related to later PD onset, mainly in females (Metcalfe-Roach et al, 2021 ). Moreover, physical activity interventions have shown improvement in functional outcomes in PD patients (Sharp and Hewitt, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…EVOO also contains pentacyclic triterpenoids such as oleanolic acid, and triglyceride fatty acids like oleic, palmitic, and linoleic acids (Javadi, 2018; Lou‐Bonafonte, Arnal, Navarro, & Osada, 2012). EVOO is the most important lipid source of the Mediterranean diet (MD), adherence to which is associated with a lower probability of PD (Javadi & Sahebkar, 2017; Maraki et al, 2019; Metcalfe‐Roach et al, 2020).…”
Section: Resultsmentioning
confidence: 99%